The Effect of Leadership, Motivation, and Work Environment on Performance of Employees at Panai Central Camat Office - Rika Rika; Rizki Syahputra; Christine Herawati Limbong (Quantitative Economics and Management Studies, 2022)
This study was conducted to determine the effect of Leadership (X1), Motivation (X2) and Work Environment on Work Performance (Y) at the Panai Tengah District Office. This research is a type of quantitative research. The population used in this study were all employees at the Panai Tengah District Office. The sample consists of 34 samples of respondents. Data were analyzed using multiple linear regression analysis techniques. The results of the study were obtained where (1) the Leadership Variable (X1) did not have a positive and significant/significant effect on work performance where the number of t count < t table was 1,943 > 2,042. (2) Motivation variable (X2) has no positive and significant/significant effect on work performance where the number of t count < t table is 0.881 < 2.042. (3) The Work Environment Variable (X3) does not have a positive and significant/significant effect on work performance where the number of t count < t table is 0.483 < 2.042. (4) Leadership (X1), Motivation (X2), and Work Environment (X3) variables have a positive and significant/significant effect on work performance (Y) simultaneously where the number of F count > F table is 3.230 > 2.922. The value of the R2 coefficient of 0.169 means that Leadership (X1), Motivation (X2), and Work Environment (X3) affect work performance by 16.9%, while 83.1% is influenced by others. F table is 3,230 > 2,922. The value of the R2 coefficient of 0.169 means that Leadership (X1), Motivation (X2), and Work Environment (X3) affect work performance by 16.9%, while 83.1% is influenced by others. F table is 3,230 > 2,922. The value of the R2 coefficient of 0.169 means that Leadership (X1), Motivation (X2), and Work Environment (X3) affect work performance by 16.9%, while 83.1% is influenced by others.